Patient satisfaction with medical care - M. A. Sadovoy; O. S. Kobyakova; I. A. Deev; E. S. Kulikov; N. A. Tabakaev; D. S. Tyufilin; O. O. Vorobyeva (Бюллетень сибирской медицины)
Patients’ evaluation of medical care is becoming more and more important due to expanding patient-centered care. For this purpose a complex index of patient satisfaction with healthcare is used. This parameter reflects the correspondence of actual healthcare services to patient’s expectations that were formed under the influence of cultural, social, economic factors, and personal experience of each patient. Satisfaction is a subjective parameter, thus, a grade of satisfaction is barely connected with quality of healthcare services itself. Moreover, medical organizations should always take into account specific features of each patient, since they can have an influence on customer attitude to medical services.This article comprises the review of publications studying determinants of patient satisfaction. In the course of the study, we analyzed data received by research teams from different countries.According to the review, we made some conclusions. First, determinants of patient satisfaction with healthcare can be divided in two groups. The first group of factors includes patients’ characteristics such as age, gender, ethnical and cultural features. However, researches from different countries revealed that there is a difference in the importance of factors belonging to this group and their influence on satisfaction of certain patient cohorts. The second group includes factors that belong to the process of healthcare services delivery and its organization. Moreover, it was found that patient satisfaction level is changing in a waveform. Thus, medical organization should not only try to increase patient satisfaction level but also maintain it. AS a result, it necessary to monitor patient satisfaction with healthcare services. That is why there is a distinct need for the development of a new tool or adaptation of existing instrument of satisfaction measurement, which would be unitized for all medical organizations in the Russian Federation